A low-cost wearable device for portable sequential compression therapy - Schara, Mark; Zeng, Mingde; Jumet, Barclay; Preston, Daniel J. (Frontiers in Robotics and AI, 2022)
In 2020, cardiovascular diseases resulted in 25% of unnatural deaths in the United States. Treatment with long-term administration of medication can adversely affect other organs, and surgeries such as coronary artery grafts are risky. Meanwhile, sequential compression therapy (SCT) offers a low-risk alternative, but is currently expensive and unwieldy, and often requires the patient to be immobilized during administration. Here, we present a low-cost wearable device to administer SCT, constructed using a stacked lamination fabrication approach. Expanding on concepts from the field of soft robotics, textile sheets are thermally bonded to form pneumatic actuators, which are controlled by an inconspicuous and tetherless electronic onboard supply of pressurized air. Our open-source, low-profile, and lightweight (58 g) device costs $62, less than one-third the cost of the least expensive alternative approved by the US Food and Drug Administration (FDA), presenting the opportunity to more effectively provide SCT to socioeconomically disadvantaged individuals. Furthermore, our textile stacking method, inspired by conventional fabrication methods from the apparel industry, along with the lightweight fabrics used, allows the device to be worn more comfortably than other SCT devices. By reducing physical and financial encumbrances, the device presented in this work may better enable patients to treat cardiovascular diseases and aid in recovery from cardiac surgeries.